Analysis of Factors Influencing Students to Enroll in Medical Record and Health Information Program at the School of Health Sciences Panakkukang Makassar, South Sulawesi - Asriyanti, .; Syamsuddin, .; Ilyas, Arief Azhari (KnE Life Sciences, 2021)
One of the principles of higher education is freedom in choosing a study program based on the student’s interests and abilities. These elements influence the student’s decisions in choosing a college/university. School of Health Sciences Panakkukang, one of the tertiary institutions organizing the D-3 Medical Records and Health Information (RMIK) Study Programs, is becoming an increasingly popular choice. This can be seen from the number of students enrolled (214 in 2016, 225 in 2017, 177 in 2018, and 122 in 2019). The students’ decision to choose the Study Program is influenced by cultural, social and personal factors. This study’s objective is to determine the effect of these factors on the selection of Study Programs. This research uses a descriptive analytic quantitative approach with a cross-sectional research design. The study population was 524 students with a sample of 84 respondents taken proportionally (20 first-year students, 28 second-year students and 36 thirdyear students). The results showed that the cultural and personal factors did not significantly influence the selection of D-3 RMIK Study Programs with sig. cultural factors of 0.595> 0.05, personal factors with sig. of 0.197> 0.05. While the social factors significantly influence the selection of D-3 RMIK Study Programs with sig. of 0.000 <0.05. The cultural, social and personal factors have a combined effect of 33.8%. Keywords: cultural, social, personal factors.